Modelling Emergency Evacuation of Classroom with Different Age Profiles - Vanumu, Lakshmi Devi; Arya, Aditya; Gaddam, Hari Krishna; Rao, K. Ramachandra (Collective Dynamics, 2020)
Evacuation characteristics of pedestrians can be captured under two different conditions - one in immediate and another in non-immediate. The safe and quick evacuation of pedestrians from a building in any situation depends on pedestrian and building characteristics. Understanding the behaviour of pedestrians in emergency situations such as earthquake or fire accident helps in designing buildings for safe evacuation. In view of the limited research on this problem in the Indian subcontinent, this study aims to capture the pedestrian flow characteristics in emergency situations by conducting several experiments in a classroom environment. As a part of the experimental study, the students were instructed to behave as if they were in an emergency evacuation situation. Data was collected on pedestrians with different age profiles such as high school, under graduate and post graduate students considering various scenarios that includes different door widths. Several factors such as number of pedestrians, width of the door, average age of the pedestrians, Body Mass Index, proportion of females, number of students and classroom capacity are considered and their influence on evacuation characteristics was analysed. Based on the observations, an evacuation model has been developed using least square error method. Results show that the variables such as door width and number of students are crucial in representing evacuation time of the classroom. It was found that the relationship between total evacuation time (TET) and door width is represented by power function. This is contrast to the findings of existing literature which shows that the relationship between flow and door width is linear. Our results are best supported by the fact that the TET is exponentially varying with door width till a particular value and remains constant for further increase in door width which is realistic in nature. It is anticipated that the results of the study would provide guidelines to various agencies on managing evacuations. This can also lead to suggestions on optimization of layouts while designing various building access facilities in an academic environment.